Association of GSTM1 and GSTT1 Null Genotypes with Toluene Diisocyanate-Induced Asthma - Jong-Uk Lee; Ji-Yeon Jeong; Min Kyung Kim; Sun A. Min; Jong-Sook Park; Choon-Sik Park (Canadian Respiratory Journal)
Background. Toluene diisocyanate (TDI) causes occupational asthma by generating oxidative stress, leading to tissue injury and inflammation. Glutathione transferases (GSTs) are detoxifying enzymes that eliminate oxidative stress. We examined whether the genotypes of the GSTM1 and GSTT1 genes are associated with TDI-induced occupational asthma (TDI-OA). Methods. The study population consisted of 26 asthmatics with a positive response to the TDI challenge (TDI-PA) and 27 asthmatics with negative responses (TDI-NA). GSTM1 and GSTT1 null and wild-type genotypes were determined using multiplex PCR. The plasma GSTM1 and GSTT1 protein concentrations were determined using ELISA. Results. The GSTM1 null genotype was more frequent in the TDI-PA than in the TDI-NA (77.8 vs. 50.0%, OR = 3.5, p=0.03), while the frequency of the GSTT1 null genotype tended to be higher in the TDI-PA than in the TDI-NA (59.3 vs. 42.3%, OR = 1.98, p=0.21). When analyzed together, the GSTM1/GSTT1 null genotype was more frequent in the TDI-PA than in the TDI-NA (48.2 vs. 15.3%, OR = 6.5, p=0.04). The decline in the FEV in 1 s after TDI challenge was higher with the GSTM1/GSTT1 null than the GSTM1 wild-type/GSTT1 null genotypes (24.29% vs. 7.47%, p=0.02). The plasma GSTM1 level was lower with the GSTM1 null than with the GSTM1 wild-type genotypes both before (13.7 vs. 16.6 ng/mg, p=0.04) and after (12.9 vs. 17.1 ng/mg, p=0.007) the TDI challenge, while the GSTT1 level was not changed with either the GSTT1 null or wild-type genotype. Conclusions. The GSTM1 null genotype, but not GSTT1 alone, may confer susceptibility to TDI-OA. However, the genetic effect of the GSTM1 null genotype may be enhanced synergistically by the GSTT1 null genotype. The genetic effect of GSTM1 was validated in the plasma as the GSTM1 protein level. Therefore, the GSTM1 and GSTT1 genotypes may be useful diagnostic markers for TDI-OA.